2005
DOI: 10.1002/jrs.1253
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Raman wavenumbers and P?O bond lengths in crystalline inorganic phosphates

Abstract: A linear empirical correlation was established between Raman stretching wavenumbers of phosphorus-oxygen bonds and their bond lengths in inorganic crystalline phosphates. Although established on samples of inorganic crystalline phosphates, the correlation can be applied to glassy and amorphous phosphate materials (GAMs). Their unpolarized vibrational spectra are often similar because they are determined largely by short-range order. The correlation was used to predict P -O bond length in the a-form of Li 3 PO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
89
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 77 publications
13
89
0
Order By: Relevance
“…9b. A Raman peak appearing at 574 and 580 cm À1 is well-known as A 1g mode intensity arises either as a consequence of increase in the surface-to-volume atom ratio or due to conversion from crystalline to nanocrystalline induced by increasing disordered atoms by milling [22]. These intensity peaks of the TGA sample are comparable to those obtained after Raman analysis of the TGA powder for the pre-annealed sample (Fig.…”
Section: Resultssupporting
confidence: 80%
“…9b. A Raman peak appearing at 574 and 580 cm À1 is well-known as A 1g mode intensity arises either as a consequence of increase in the surface-to-volume atom ratio or due to conversion from crystalline to nanocrystalline induced by increasing disordered atoms by milling [22]. These intensity peaks of the TGA sample are comparable to those obtained after Raman analysis of the TGA powder for the pre-annealed sample (Fig.…”
Section: Resultssupporting
confidence: 80%
“…The shifts however, observed between our vibrational frequencies and those reported by Harada et al (1971), Arkhipenko and Moroz (1997), and Socrates (2001) reflect the partial substitution of (SiO 4 ) 4-and (SO 4 ) 2-for the (PO 4 ) 3-group in the apatite structure. Based on Santos and Clayton (1995) and Popović et al (2005), the IR bands at 1144 and 1049 cm -1 from our spectrum were assigned to either double or single bond stretching of an orthophosphate and not to the (SO 4 ) 2-group as suggested by Harada et al (1971) and Sejkora et al (1999).…”
Section: Al-o2supporting
confidence: 55%
“…Popovic et al have shown that the positions of Raman peaks from crystalline inorganic phosphates correlates with the P-O bond length, where generally longer bonds are associated with lower wavenumbers [25]. If a similar correlation exists for the modified zinc phosphate glasses, then the decrease in the (PO 2 ) sym peak position of the modified glasses shown in Fig.…”
Section: Confocal Raman and Fluorescence Microscopymentioning
confidence: 83%